Autosomal recessive cerebellar ataxias - Palau, Francesc (BioMed Central, 2006)
Autosomal recessive cerebellar ataxias (ARCA) are a heterogeneous group of rare neurological disorders involving both central and peripheral nervous system, and in some case other systems and organs, and characterized by degeneration or abnormal development of cerebellum and spinal cord, autosomal recessive inheritance and, in most cases, early onset occurring before the age of 20 years. This group encompasses a large number of rare diseases, the most frequent in Caucasian population being Friedreich ataxia (estimated prevalence 2–4/100,000), ataxia-telangiectasia (1–2.5/100,000) and early onset cerebellar ataxia with retained tendon reflexes (1/100,000). Other forms ARCA are much less common. Based on clinicogenetic criteria, five main types ARCA can be distinguished: congenital ataxias (developmental disorder), ataxias associated with metabolic disorders, ataxias with a DNA repair defect, degenerative ataxias, and ataxia associated with other features. These diseases are due to mutations in specific genes, some of which have been identified, such as frataxin in Friedreich ataxia, α-tocopherol transfer protein in ataxia with vitamin E deficiency (AVED), aprataxin in ataxia with oculomotor apraxia (AOA1), and senataxin in ataxia with oculomotor apraxia (AOA2). Clinical diagnosis is confirmed by ancillary tests such as neuroimaging (magnetic resonance imaging, scanning), electrophysiological examination, and mutation analysis when the causative gene is identified. Correct clinical and genetic diagnosis is important for appropriate genetic counseling and prognosis and, in some instances, pharmacological treatment. Due to autosomal recessive inheritance, previous familial history of affected individuals is unlikely. For most ARCA there is no specific drug treatment except for coenzyme Q10 deficiency and abetalipoproteinemia.